Sistem Akuisisi Data Multiplatform Berbasis PC dengan Tampilan Hasil di Twitter - Arief Hendra Saptadi (Universitas Syiah Kuala, 2015)
Computer or Personal Computer (PC) based data acquisition system had enabled the measurement of physical parameters, not only to display and store them in the computer but also to send them to a website. Twitter as one of web services for social media that provides the facility to display 140-character length of text status has been deemed sufficient for the purpose of displaying the latest data and is accessible through available Application Programming Interface (API). The purpose of this research is to design a PC-based data acquisition system which is capable to conduct measurement, storage and transmission of data to the web service via Twitter API. The proposed system was consisted of LM35 temperature sensor to measure room temperature, Arduino Nano microcontroller and a data acquisition application in PC to display and store data in a Comma-Separated Values (CSV) file. Based on test results for processes involving Analog to Digital Converter (ADC), the obtained error is 3.71% for voltage value and the average difference between measured values and displayed ones is 0.01 V. Average error for temperature measurement is 5.13% and the difference between measured values and the displayed ones is 1.34°C. Built application had produced an adequate display of interface and fulfilled all required functionalities. Average response time of Twitter API to Choreo is 0.18 s while average time to transmit data from application to Twitter is 2.15 s or 11.75 times longer. In later development, LM35 should be replaced with a more precise sensor. The occurrence of randomness in measurement results could be minimized by adding an active filter circuit between sensor and microcontroller.